Analisis Munculnya Kebijakan Luar Negeri Prancis terhadap Imigran Asing Tahun 2017-2023 Akibat Faktor-Faktor Domestik dan Internasional - Sianipar, Marcello; Perbawani, Firsty Chintya Laksmi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to analyze French foreign policy towards foreign immigrants in 2017-2023 using the Foreign Policy Change theory proposed by Eidenfalk. This research methodology is a qualitative study with a descriptive approach. Data were obtained from literature studies: government reports, journals, and news. The results of this study indicate that domestic factors: bureaucracy, public opinion, media, and French right-wing parties view immigrants negatively and need to reduce their access to France. International factors: non-state actors, namely the issue of terrorism entering as immigrants in France. However, from international factors: the 1951 Geneva Convention, the 1967 Protocol, and the European Union which requires France to assist foreign immigrants on humanitarian grounds and maintain bilateral cooperation with other countries. Based on these factors, The Asylum and Immigration Act of 2018 was formed, namely a foreign policy towards foreign immigrants that is restrictive, but still accepts foreign immigrants who meet the criteria and deserve access. Thus, France's foreign policy towards foreign immigrants in the period 2017–2023 is the result of a compromise between domestic pressures that encourage tightening of immigration and international obligations that demand humanitarian protection, which is reflected in the selective and restrictive implementation of the Asylum and Immigration Act 2018. Keywords: Domestic Factors, Foreign Policy, International Factors.